Konflik Komunal: Maluku 1999-2000 - Jamin Safi (Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to explain the conflict Ambon, political upheaval in North Maluku to ethnic and religious conflicts 1999-2000. This study uses historical method. Historical research includes five stages: topic selection, heuristics, criticism, interpretation, and historiography. The conflict that occurred since 19 January 1999 Maluku is a bloody event that coincides with Muslims celebrating the Eid al-Fitr 1419 Hijri. The conflict stems from a dispute between an angkot driver, a Christian Jacob Lauhery with Nursalim, an Islam of the Bugis Red Stone. Conflict then developed into religious conflict (Islam and Christian). In North Maluku conflicts also occur, local political upheaval, North Maluku causing polarization in society to ethnic and religious conflicts. The North Maluku conflict is also part of a power struggle. Another factor is the creation of a new sub-district of Makian Malifut based on PP. No.42 / 1999 has been rejected by the Kao community because it is considered contrary to customary law. The event spread to Tidore, Ternate, Jailolo and Bacan. The North Maluku conflict claimed thousands of lives, homes and places of worship, both Muslims and Christians burned. During the conflict, Pela Gandong in Ambon, Maluku and indigenous people in Maluku Kie Raha as a customary and cultural system no longer functions as a strong social bond. Keywords: Conflict, Communal, Maluku, Ethnicity